Quantum Backaction on Kg-Scale Mirrors: Observation of Radiation Pressure Noise in the Advanced Virgo Detector - Acernese, F.; Agathos, M.; Aiello, L.; Ain, A.; Allocca, A.; Amato, A.; Ansoldi, S.; Antier, S.; Arène, M.; Arnaud, N.; Ascenzi, S.; Astone, P.; et al. (Physical review letters, 2020)
The quantum radiation pressure and the quantum shot noise in laser-interferometric gravitational wave detectors constitute a macroscopic manifestation of the Heisenberg inequality. If quantum shot noise can be easily observed, the observation of quantum radiation pressure noise has been elusive, so far, due to the technical noise competing with quantum effects. Here, we discuss the evidence of quantum radiation pressure noise in the Advanced Virgo gravitational wave detector. In our experiment, we inject squeezed vacuum states of light into the interferometer in order to manipulate the quantum backaction on the 42 kg mirrors and observe the corresponding quantum noise driven displacement at frequencies between 30 and 70 Hz. The experimental data, obtained in various interferometer configurations, is tested against the Advanced Virgo detector quantum noise model which confirmed the measured magnitude of quantum radiation pressure noise.